Analisis Tantangan dan Peluang dalam Pengembangan Produk Investasi Syariah (Studi Kasus Di BSI KCP Pinrang) - Amaliah Nur Wahida; Wahyuni; Rasyidah Bulqis (Mappideceng:Jurnal Ekonomi Syariah, 2025)
Along with the development of the sharia financial industry, especially in the banking sector, sharia investment products have become one of the choices that  are increasingly in demand by the public. However, the development of this product cannot be separated from the various challenges that must be faced, both in terms  of regulation, understanding, and market competition in the community. This study aims to determine the development, challenges and opportunities of sharia investment products. The type of research used is descriptive qualitative. In its implementation, researchers conducted field visits to collect relevant information from employees of Bank Syariah Indonesia Pinrang Branch. The results of this study are. 1) The development of sharia investment products at Bank Syariah Indonesia focuses on two main products, namely gold installments and deposits. The emphasis on increasing gold installment sales and strengthening deposit products is expected to strengthen the position of sharia banking in the Pinrang Regency area. 2) the challenges in the gold installment program at Bank Syariah Indonesia (BSI) KCP Pinrang are related to the down payment (DP) which is often an obstacle for some customers